Direito à educação da pessoa com deficiência: ações judiciais em uma comarca do estado de São Paulo (2015-2020) - Barros, Sheila Lopes de (2023)
The right to education in the Federal Constitution of 1988 is declared as a fundamental right, of a social nature, constituting a right for all and a duty of the State and the family. The recognition of education as a duty of the State imposes on this entity the elaboration and implementation of public policies to achieve this right. In the context of Brazilian constitutionalism, with the expansion of access to justice, if this right is not guaranteed through public policies, resorting to the Judiciary can be a way to make it effective. Considering the phenomenon of judicialization and accompanying the legal demands regarding the education of students with disabilities, the present work has the general objective of presenting an overview of the legal actions that concern Special Education filed in a district of the Court of Justice of the state of São Paulo (TJSP), from 2015 to 2020, in order to discuss trends in judicialization in guaranteeing the right to education for this population. In order to achieve this objective, we sought to: identify and characterize the settlements of lawsuits and the decisions handed down; examine the themes that refer to the auxiliary teacher and vacancy ins a special school, in view of the expressive number of lawsuits filed; to analyze the medical, pedagogical and legal discourse of the right to education for people with disabilities within the scope of the TJSP. It is a documental research quantitative and qualitative character, whose corpus is constituted by 85 (eighty-five) actions. For analysis and treatment of data, support was sought in elements of Discourse Analysis. From the analyzed data, it was possible to verify a growing search for the Judiciary in the delimited time frame and its performance in the realization of the right to education of students with disabilities. The results indicate that, as a rule, the actions filed regarding Special Education are granted and are characterized by requests that meet individual interests, with limited repercussions. It appears that the medical report is the basic probative document for the judicial decision. Furthermore, it is observed that the medical evaluation report adopts a conception of disability based on the International Classification of Diseases (ICD), anchoring itself in the traditional medical model focused on the disease, despite the progress obtained with the definition of the International Classification of Functioning (CIF), which considers the health condition from the context in which the person is inserted. Although the medical report guides the judicial process, the TJSP also relies on expert pedagogical evaluation to analyze most requests. It appears that the pedagogical opinions are drawn up from a social conception of disability and highlight aspects related to the student’s surroundings and school barriers that impede learning. However, it is noted that the pedagogical opinions accompany the recommendations contained in the medical report regarding the locus of schooling of people with disabilities and the necessary support, which portrays the historical weight of the clinical approach (medical-psychological) on the area of Education and of Special Education. It is considered that the tendency to have an expert pedagogical evaluation may provoke tensions and broaden perspectives to open other cracks in the judicialization of Special Education, in the sense of promoting prospective actions based on the collectivity and organization of the school.